The Effect of Histological Subtypes on Outcomes of Stage IV Epithelial Ovarian Cancer - Zhou, Juan; Wu, San-Gang; Wang, Jun; Sun, Jia-Yuan; He, Zhen-Yu; Jin, Xin; Zhang, Wen-Wen (Frontiers in Oncology, 2018)
Introduction: To examined survival outcome by histological subtypes in de novo stage IV epithelial ovarian cancer (EOC). Methods: Between 2004 and 2015, patients with stage IV EOC were included using the Surveillance, Epidemiology, and End Results program. The effects of histological subtypes on overall survival (OS) were assessed using Kaplan–Meier and multivariable Cox regression analyses. Results: We identified 5953 patients including 5351 (89.9%), 249 (4.2%), 145 (2.4%), and 208 (3.4%) patients with high-grade serous, endometrioid, mucinous, and clear cell subtypes, respectively. The 5-year OS rates were 28.1%, 38.6%, 14.2%, and 18.8% in patients with high-grade serous, endometrioid, mucinous, and 18.8% clear cell subtypes, respectively (p < 0.001). Multivariate analyses indicated that histological subtype was an independent predictor of OS. Using the high-grade serous subtype as a reference, OS was comparable for the endometrioid subtype (hazard ratio (HR) 0.915, 95% confidence interval (CI) 0.772-1.085, p = 0.305), but significantly lower for mucinous (HR 3.292, 95% CI 2.701-4.011, p < 0.001) and clear cell subtypes (HR 1.820, 95% CI 1.546–2.141, p < 0.001). Patients with no residual tumor had better OS in the high-grade serous and endometrioid subtypes compared to patients with residual tumors. However, the residual tumor size was not a prognostic factor for OS in mucinous and clear cell carcinoma. Conclusions: Our study suggest a markedly mortality rate in patients with stage IV mucinous and clear cell carcinoma, but better survival in patients with high-grade serous and endometrioid subtypes. Aggressive radical surgery to leave no residual disease would improve survival for high-grade serous and endometrioid carcinoma. More studies are needed to assess the value of aggressive radical surgery in patients with mucinous and clear cell subtypes.